Utilizing modulating-temperature setpoints to save energy and maintain alliesthesia-based comfort. Issue 2 (17th February 2019) - Traylor, Caleb; Zhao, Weihuan; Tao, Yong X.
ABSTRACT: One area with the greatest potential for energy savings in buildings is heating and cooling. However, it is often argued that any energy-saving techniques should not have a negative impact on comfort for inhabitants. This is where the concept of alliesthesia comes into play. This paper examines the impact of utilizing modulating temperature setpoints to take advantage of the pleasure experienced through change. Simulations were conducted using EnergyPlus to explore the potential for energy savings. It was found that savings of up to 5–15% could be achieved by modulating indoor temperatures in cooling applications. However, modulating temperature setpoints resulted in larger energy usage than constant setpoints in heating applications. Results from human comfort experiments show that modulating temperatures could lead to greater thermal pleasure than a constant temperature environment for cooling situations due to a resetting of the thermal comfort achieved when the indoor temperature is decreased. However, the same comfort benefits are not shown for heating situations. Nonetheless, the simulations and the comfort experiments together show potential for both energy savings and increased human comfort levels in cooling applications.